THE EFFECT OF CORN WASTE COMPOST ON THE GROWTH AND YIELD OF VIGNA SINENSIS ON ALLUVIAL - meko, albertus; zulfita, dwi; mustamir, elly (Jurnal Sains Mahasiswa Pertanian, 2019)
ABSTRACTThis study aims to find the best compost dose of corn waste on the growth and yield of vigna sinensis plants on alluvial soil. The research was carried out from 25 January 2019 - 21 March 2019. The research was conducted on Jl. Purnama Agung VII, Komplek Pondok Agung Permata, Parit Tokaya Village, South Pontianak. The method used was a Completely Randomized Design (CRD) consisting of 5 treatments, 5 replications and each replication there were 4 plant samples. The following treatment p1 = 5 tons compost of corn waste / ha or equivalent to 100 gr / polybag, p2 = 10 tons compost of corn waste / ha is equivalent to 200 g / polybag, p3 = 15 tons compost of corn waste / ha equivalent to 300 g / polybag , P4 = 20 tons compost of corn waste / ha is equivalent to 400 g / polybag, P5 = 25 tons tons compost of corn waste / ha is equivalent to 500 g / polybag. The variables observed in this study were Root Volume (cm3), Chlorophyll Leaf Level (spad unit), Plant Dry Weight (g), Fruit / Plant (fruit) and Fruit Weight / Plant (g). The results showed that the best compost of corn waste for growth and yield of lvigna sinensis was 400 g / polybag, equivalent to 20 tons / ha but the variable fruit weight of pods per plant was not significant at a dose of 100 g / polybag or equivalent to 5 tons / Ha. Therefore, in this study, the effective dose of corn waste compost was found to be100 g / polybag, equivalent to 5 tons / ha.Keywords: Alluvial, Corn waste compost, vigna sinensis.